FACTORS AFFECTING THE AL WASHLIYAH COMMUNITY IN CHOOSING ISLAMIC INSURANCE IN NORTH SUMATRA - Fauzi Arif Lubis; HM. Yasir Nasution; Andri Soemitra (State Islamic University of North Sumatra Indonesia, 2020)
This study aims to reveal the Al Washliyah community's preference for sharia insurance in North Sumatra, which is focused on aspects: How far do the cultural and personality significantly affect their preference for sharia insurance in North Sumatra. This study uses a quantitative approach by looking at latent variables and manifest variables together against Al Washliyah's community preferences for sharia insurance. Data were collected using a Likert scale model questionnaire taken from a sample of 374 peoples. Data analysis using Structural Equation Modelling (combined factor analysis with regression analysis) with the help of Lisrel Program. The results revealed that variable factors culture, subculture, and social class are valid and reliable in shaping latent Culture variables. Life cycle factors, economic environment, self-concept, and lifestyle are valid and reliable in forming latent variables of Personality. Preference is significantly related to Culture by 0.67, while the influence / coefficient of determination (R2) is = 0.45 and Contribution by 45%. Preference is significantly related to Personality of 0.33, the influence/coefficient of determination (R2) of = 0.11 and its contribution of 11%. Based on these findings, it is expected that institutions that have sharia insurance products in order to be able to pay attention to factors that make people choose sharia insurance products such as: culture and personality so that sharia insurance products can be in demand, especially for the peoples/residents of Al Washliyah. Keywords: Al Washliyah Community, Islamic insurance